Delight or Distraction: An Exploratory Analysis of Sabbath-Keeping Internalization - Bailey, Karl G. D. (Journal of psychology and theology, 2015)
Internalization of religious motivation is associated with increased subjective well-being. However, much of the work on internalization focuses on widespread, low-cost religious practices. We propose that distinctive, high-cost, and meaningful Christian practices, such as Sabbath keeping, may be related to the internalization of religion—and thus increased well-being—when they occur within a community. Using a factor-cluster approach to develop an instrument to measure the internalization of Sabbath keeping among Seventh-day Adventists, we found a positive relationship between deeper internalization and higher subjective well-being. Importantly, the relationship between internalization of Sabbath-keeping practice and well-being was only weakly meditated by a more general measure of religious internalization, suggesting separate contributions of internalization for distinctive high-cost practices and widespread low-cost practices.